(untitled) (River Edge, N.J.,London, 2004)
This book collects together refereed versions of papers presented at the Eighth Neural Computation and Psychology Workshop (NCPW 8). NCPW is a well-established workshop series that brings together researchers from different disciplines, such as artificial intelligence, cognitive science, computer science, neurobiology, philosophy and psychology. The articles are centred on the theme of connectionist modelling of cognition and perception.
Keywords: Neural networks (Neurobiology),Neural computation,Neural networks (Computer science),Mạng nơron,Mạng nơron; Psychological aspects,Khía cạnh tâm lý học